Molecular epidemiology of Panton- Valentine Leukocidin-positive community-acquired methicillin resistant Staphylococcus aureus isolates in pastoral communities of rural south western Uganda - Asiimwe, Benon B.; Baldan, Rossella; Trovato, Alberto; Daniela, M. Cirillo (BMC infectious diseases, 2017)
The emergence of multidrug resistant Staphylococcus aureus strains, including methicillin resistant (MRSA), is a global concern. Treatment of bacterial infections in Uganda’s health care settings is largely empirical, rarely accompanied by laboratory confirmation. Here we show the burden, characteristics of MRSA and epidemiology of Panton-Valentine Leukocidin (PVL) positive strains in asymptomatic carriers in pastoral households of south-west Uganda. Nasal swabs from 253 participants were cultured following standard methodology. MRSA strains were identified by detection of the mecA gene and SCCmec typing, and PVL genes detected by PCR. Pulsed Field Gel Electrophoresis (PFGE) was done to evaluate possible transmission patterns. Spa typing of PVL positive isolates was done to study the epidemiology of virulent strains in this setting. S. aureus was isolated in 29% (n = 73) of the participants, of which 48 were MRSA by mecA typing. PVL-encoding genes were found in 49.3% (n = 36) of the 73 isolates, of which 25 were also mecA positive. Among the PVL negative strains (n = 37), 62.2% (n = 23) carried the mecA gene. The most common SCCmec type was V, detected in 39 (18 PVL positive and 21 PVL negative) isolates. PFGE clustered 21/36 (58.3%) PVL positive isolates divided in four pulsotypes and 18/37 (48.6%) PVL negative isolates divided in eight pulsotypes. The most prevalent Spa types were t318 (26.5%, n = 9) and t645 (20.6%, n = 7); while other common Spa types were t11656 (n = 3), t127 (n = 3) and t355 (n = 3). The study shows a high prevalence of community acquired (CA)-MRSA, and PVL-positive isolates with two predominant spa types in rural Uganda, further complicating infection control strategies in these underprivileged communities.